The effect and mechanism of IL-37d on neutrophil recruitment in the early stage of tumor metastasis in the lungs - Yetong Guan; Chang Gao; Yan Guo; Meifang Wang; Lining Zhang (Discover Oncology)
Abstract Background Chronic inflammation plays a pivotal role in cancer progression, with tumor-associated neutrophils (TANs) actively shaping the pre-metastatic niche. Interleukin-37 (IL-37), a known immunosuppressive cytokine, is implicated in this regulation, although its precise function remains underexplored.Therefore, this study seeks to further elucidate the inhibitory effect of IL-37d on neutrophil recruitment within the pre-metastatic lung microenvironment and its underlying mechanisms, thereby providing a theoretical foundation for clinical interventions in the early stages of cancer progression. Methods This study investigates the impact of IL-37d on tumor growth, metastasis, and survival in a murine model, with a focus on the molecular mechanisms involved. Specifically, we explored IL-37d's ability to inhibit toll-like receptor 3 (TLR3) activation in lung epithelial cells, reduce calcium-binding proteins S100A8/A9 (S100a8/9) expression, and suppress matrix metalloproteinase 9 (MMP9) activity. We also examined IL-37d’s effect on neutrophil migration from the bone marrow to the lungs during early metastasis. Results IL-37d treatment significantly reduced lung metastasis and extended survival in mice. Mechanistically, IL-37d inhibited TLR3 activation, downregulated S100a8/9 expression, and reduced MMP9 activity, thereby impairing the migration of bone marrow-derived neutrophils to the lungs. This led to decreased neutrophil infiltration and a disruption of the pre-metastatic niche formation. Conclusion Our study represents the first investigation into the role of IL-37d in inhibiting tumor metastasis during the early stages by suppressing S100A8/9 and MMP9 expression in lung tissue, thereby reducing neutrophil recruitment and spontaneous migration from the bone marrow.